RAINWATER REUSE IN RESIDENCES:: A SUSTAINABLE ALTERNATIVE FOR THE MANAGEMENT OF WATER RESOURCES - Paulo Henrique de Sousa (Journal of Interdisciplinary Debates, 2023)
The reuse of rainwater in households is a sustainable alternative for water resource management, aiming to preserve potable water and reduce waste. Despite facing technical, financial, and regulatory challenges, this practice can contribute to sustainable water resource management, generating environmental, social, and economic benefits. It is essential for society to become aware of the importance of water resource preservation and adopt measures for sustainable management.